Sombreamento dos cafèzais II: resultados do 4.° biênio (1959/1960) - Godoy Junior, C.; Graner, E. A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
This paper deals with data obtained in 1959 and 1960 in shaded and unshaded coffee plots at Piracicaba, São Paulo, Brazil. The results can be summarized as follows: a) the production, in shaded and unshaded plots, did not show differences statisticaly significant; b) the percentage of coffee berry borer infestation was higher in shaded plots as compared with unshaded ones; c) the percentage of green, ripened and dry fruits depends of the year and of the harvest time. In the same harvest time, both for shaded and for unshaded plots the percentages in the shaded plots were higher for green fruits and lesser for ripened and dry fruits; d) coffee fruits brought from the field in the harvest time yielding up in unshaded plots as compared with shaded ones; e) the relation grains/dry fruits was better in shaded plots.